2015
DOI: 10.1002/anie.201411857
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Self‐Sorting Self‐Assembly Formation of a [4:4] Sulfate:Ligand Cage from a Preorganized Tripodal Urea Ligand

Abstract: The design and synthesis of tripodal ligands 1-3 based upon the N-methyl-1,3,5-benzenetricarboxamide platform appended with three aryl urea arms is reported. This ligand platform gives rise to highly preorganized structures and is ideally suited for binding SO4 (2-) and H2 PO4 (-) ions through multiple hydrogen-bonding interactions. The solid-state crystal structures of 1-3 with SO4 (2-) show the encapsulation of a single anion within a cage structure, whereas the crystal structure of 1 with H2 PO4 (-) showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 46 publications
0
39
0
Order By: Relevance
“…We considered exploiting the unique btp – btp hydrogen‐bonding features of 3 for anion recognition: an area that we have been actively exploring . Although triazoles have not been widely exploited in catenane synthesis, they are often used in the synthesis of anion receptors owing to their hydrogen‐bond‐donor ability .…”
Section: Methodsmentioning
confidence: 99%
“…We considered exploiting the unique btp – btp hydrogen‐bonding features of 3 for anion recognition: an area that we have been actively exploring . Although triazoles have not been widely exploited in catenane synthesis, they are often used in the synthesis of anion receptors owing to their hydrogen‐bond‐donor ability .…”
Section: Methodsmentioning
confidence: 99%
“…Pandurangan et al 78 have recently reported an interesting example of self-sorting self-assembly of a 4:4 sulfate ligand cage. Proton NMR titrations were performed with SO 4 2À and revealed that 155-157 form both a 2:1 receptor-sulfate complex and, at higher anion concentrations, a 1:1 complex.…”
Section: Self-assembling Systems Involving Anionsmentioning
confidence: 99%
“…In 2015, Pandurangan et al 18 reported the design and synthesis of three tripodal receptors, 4 – 6 , based upon an N-methyl-1, 3, 5-benzenetricarboxamide platform bearing three appended aryl urea arms. The complexation and self-assembly of these three receptors with various anions (SO 4 2− , H 2 PO 4 − , AcO − , and Cl − ) was studied.…”
Section: Acyclic Anion Receptorsmentioning
confidence: 99%